Manufacture of palm oil-based degreaser for metal cleaning / Ahmad Rozaimee Mustaffa, Ku Halim Ku Hamid and Roslina Ramli - Mustaffa, Ahmad Rozaimee; Ku Hamid, Ku Halim; Ramli, Roslina (2008)
Degreaser is widely used as a cleaning agent especially for metal parts in oil and gas industries. Most of these products contain chlorinated solvents such as 1,1,1-trichloroethane or non chlorinated solvents such as methyl ethyl ketone and used as degreaser for removing contaminants from metals surface. Chlorinated and non- chlorinated solvents have been found to be environmentally unfriendly due to groundwater contamination or volatile organic compound (VOC) emission. The use of halogen, carbon tetrachloride and CFCs as degreasing agents increase overall risks to human health and also contributes to the enhancement of ozone depletion. The main objective of this project is to develop palm-oil based degreaser (POD) as an alternative product that provide the same degreasing effect as conventional commercial degreaser. The materials were selected mainly from plant- based derivatives such as fatty acids ester. POD has been compared with conventional commercial degreaser for performance testing. The results showed that the percentage of oily soil removed after cleaning process by POD was 97.27 per cent at level surfactant addition of 14 per cent. The comparative study of oily soil removal for POD decreased from 94.30 per cent to 45.22 per cent with increasing number of panels. Meanwhile, the commercial degreasers such as hydrocarbon, citrus and alkaline-based decreased of oily soil removal from 95.45 per cent to 51.74 per cent, 80.45 per cent to 40.66 per cent and 95.51 per cent to 51.36 per cent respectively with increasing number of panels.